Patient rescue and blood utilization in the Ogasawara blood rotation system. Issue 3 (7th January 2018) - Igarashi, Tomoko; Fujita, Hiroshi; Asaka, Hiroyuki; Takada, Yuko; Ametani, Rieko; Naya, Itsuki; Tanaka, Yasushi; Kamesaki, Makoto; Kasai, Asuka
Abstract : BACKGROUND: In the past, blood products were not transported to the Ogasawara Islands because of the distance; the islands are approximately 1000 km from the mainland and lack an airport. The Ogasawara Blood Rotation system involves the routine, long‐distance transportation of Type O, RhD‐positive, irradiated red blood cells to rescue patients with acute hemorrhage and severe anemia and to reduce wastage from the expiration of red blood cell solution. STUDY DESIGN AND METHODS: Blood transfusion and utilization in the Ogasawara blood rotation (BR) system were examined from December 2014 to March 2017. Two packs of RBC solution (one pack = 280 mL) were transported in an active transport refrigerator by scheduled ships between Tokyo City and the Ogasawara Islands. RESULTS: Eight packs of red blood cell (RBC) solution were received as transfusions by four patients who had acute upper gastrointestinal bleeding or severe anemia (eight of 232 packs; 3.4%). The blood utilization rate at the time of re‐use was 84.6% (196 of 232 packs), with neither adverse reactions nor wastage. Twenty‐eight packs of RBC solution expired because of a delay in scheduled ships as the result of a typhoon (12.1%). CONCLUSION: The Ogasawara BR system was effectively capable of delivering RBC solution for transfusion in patients residing in distant islands and contributed to reducing the wastage of RBC solution by facilitating blood utilization at another hospital.